Sequential Helicobacter pylori eradication therapy in Myanmar; a randomized clinical trial of efficacy and tolerability. Issue 4 (5th December 2019) - Myint, Nan Phyu Sin Toe; Zaw, Thet Tun; Sain, Kyauk; Waiyan, Soe; Danta, Mark; Cooper, David; Aung, Ne Myo; Kyi, Mar Mar; Hanson, Josh
Abstract: Background and Aim: There is little published research to examine the best approach to the management of Helicobacter pylori in Myanmar. This study aimed to determine the relative efficacy and tolerability of sequential eradication therapy compared to Myanmar's current recommendation of a concomitant four drug regimen. Methods: Patients were screened for H. pylori using monoclonal Stool Antigen Testing (SAT). Those testing positive were randomized 1:1 to receive receive Myanmar's first‐line regimen of 14 days of concomitant rabeprazole, clarithromycin, amoxycillin and tinidazole (140 pills, cost US$23) or 10 days of sequential rabeprazole, clarithromycin, amoxycillin and tinidazole (60 pills, cost US$10). Adherence and adverse effects were recorded, and the efficacy of the regimens assessed with repeat SAT. Results: Of the 1011 patients screened for H. pylori infection, 313 (31%) tested positive. There was no statistical difference in the cure rates of the two regimens in either intention‐to‐treat: 128/157 (82%; 95% confidence interval (CI): 75–87%) receiving sequential therapy versus 123/156 (79%; 95% CI: 72–85%) receiving concomitant therapy ( P  = 0.55) or per‐protocol analysis: 125/131 (95%; 95% CI: 90–98) receiving sequential therapy versus 121/130 (93%; 95% CI: 87–96) receiving concomitant therapy ( P  = 0.42). Side effects of therapy were reported in 54/157 (47%) patients taking sequential therapy compared with 62/156 (53%) taking concomitant therapy, but this difference did not reach statistical significance ( P  = 0.33). Conclusions: In this high‐burden, resource‐poor setting, less expensive sequential therapy was as effective and as well tolerated as the currently recommended concomitant four drug regimen for eradication of H. pylori .